Efficacy of different dietary therapy strategies in active pediatric Crohn’s disease: a systematic review and network meta-analysis - Jiaze Ma; Jinchen Chong; Zhengxi Qiu; Yuji Wang; Tuo Chen; Yugen Chen (PeerJ)
Background Dietary therapy strategies play an important role in the treatment of pediatric patients with Crohn’s disease (CD), but the relative efficacy of different dietary therapy strategies for Crohn’s remission is unknown. This study aims to compare the effectiveness and tolerance of these dietary therapy strategies for active pediatric CD. Methods We searched the medical literature up to August 30, 2024 to identify randomized controlled trials (RCTs) of dietary therapy strategies for pediatric CD. The primary outcomes were clinical remission rate and tolerance, secondary outcomes included differences between pre- and post-treatment levels of albumin, C-reactive protein (CRP), and fecal calprotectin levels. A network meta-analysis (NMA) was performed by using the frequentist model. For binary outcome variables and continuous outcome variables, odds ratios (OR) and mean differences (MD) with corresponding 95% confidence intervals (CI) were utilized, respectively. The ranking of dietary therapy strategies was determined based on the surface under the cumulative ranking area (SUCRA) for each comparison analyzed. Results Overall, 14 studies involving 564 participants were included. In terms of clinical remission rate, the partial enteral nutrition (PEN) plus Crohn’s disease exclusion diet (PEN+CDED) (OR = 7.86, 95% CI [1.85–33.40]) and exclusive enteral nutrition (EEN) (OR = 3.74, 95% CI [1.30–10.76]) exhibited significant superiority over PEN alone. The tolerance of PEN+CDED was significantly higher than that of EEN (OR = 0.07, 95% CI [0.01–0.61]). According to the surface under the cumulative ranking area (SUCRA) values, the PEN+CDED intervention (90.5%) achieved the highest ranking in clinical remission rate. In terms of tolerance, PEN+CDED ranked first (88.0%), while EEN ranked last (16.3%). Conclusions In conclusion, PEN+CDED was associated with the highest clinical remission rate and tolerance among the various dietary therapy strategies evaluated. Despite limitations in the studies, this systematic review provides evidence that PEN+CDED can be used as an alternative treatment to exclusive enteral nutrition and is more suitable for long-term management in children.